Bilingual Colombia: What does It Mean to Be Bilingual within the Framework of the National Plan of Bilingualism? Colombia Bilingüe: ¿Qué significa ser bilingüe en el marco del Plan Nacional de Bilingüismo? - Carmen Helena Guerrero (Universidad Nacional de Colombia, 2008)
This article is a partial research report of a critical discourse analysis of the document "Estándares básicos de competencias en lenguas extranjeras: inglés. Formar en lenguas extranjeras: ¡el reto!" (Basic standards for competences in foreign languages: English. Teaching in foreign languages: The challenge!). The analysis was informed by theory on critical discourse analysis (CDA) and on symbolic power (particularly language as symbolic power). In an attempt to interpret what it means to be bilingual in Colombia according to this document, the data show that 1) Being bilingual means speaking English; and 2) Bilingualism is constructed as a packed, monolithic and homogeneous concept. El presente artículo es un reporte parcial de un análisis crítico del discurso del documento "Estándares básicos de competencias en lenguas extranjeras: inglés. Formar en lenguas extranjeras: ¡el reto!". El análisis estuvo iluminado por teorías en análisis crítico del discurso (ACD) y la teoría de poder simbólico, particularmente la lengua como poder simbólico. En el intento por interpretar qué significa el bilingüismo en Colombia de acuerdo a este documento, los datos muestran lo siguiente: 1) Ser bilingüe significa hablar inglés y, 2) El bilingüismo se presenta como un concepto monolítico y homogéneo.